Effects of Electrochromic Glass on Computer Vision Syndrome. (September 2018) - Hedge, Alan; Nou, Danny
Occupant surveys were conducted in 4 office buildings, 2 with traditional non-tinted low-e glass (LeG) and 2 with electrochromic glass (EC). 106 employees working in these buildings volunteered to participate in the study. Results showed that subjective reports of overall ambient lighting conditions were comparable in the buildings. However, EC optimizes daylight and reduces sunlight glare, and significantly more workers sat close to the windows in the EC buildings compared to the LeG buildings. Workers in the EC office buildings reported significantly better daylight, significantly less adverse glare, and significantly fewer symptoms of computer vision syndrome than those in the LeG buildings.